Science experiments you can eat - Cobb, Vicki (Harmondsworth: Penguin, 1974)
Experiments with food demonstrate various scientific principles and produce an eatable result. Includes fruit drinks, grape jelly, muffins, chop suey, yogurt, and junket.
Keywords: Science -- Experiments -- Juvenile literature; Cookery -- Juvenile literature